2021
DOI: 10.1155/2021/6614356
|View full text |Cite
|
Sign up to set email alerts
|

Use of Innovative SPECT Techniques in the Presurgical Evaluation of Patients with Nonlesional Extratemporal Drug-Resistant Epilepsy

Abstract: Up to 30% of patients with epilepsy may not respond to antiepileptic drugs. Patients with drug-resistant epilepsy (DRE) should undergo evaluation for seizure onset zone (SOZ) localization to consider surgical treatment. Cases of drug-resistant nonlesional extratemporal lobe epilepsy (ETLE) pose the biggest challenge in localizing the SOZ and require multiple noninvasive diagnostic investigations before planning the intracranial monitoring (ICM) or direct resection. Ictal Single Photon Emission Computed Tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Smaller studies have found similar positive predictive value [76.9% - ( 165 )]. The ability of SISCOM to accurately localize a seizure focus ranged from 73 to 85% (mean 77.3%) across multiple studies ( 164 172 ). A meta-analysis of 11 studies found SISCOM accurately localized seizure focus in 85.9% of cases and was concordant with EEG data in 65.3% of cases ( 166 ).…”
Section: Assessment Of the State Of The Art—spect In Brain Disordersmentioning
confidence: 99%
“…Smaller studies have found similar positive predictive value [76.9% - ( 165 )]. The ability of SISCOM to accurately localize a seizure focus ranged from 73 to 85% (mean 77.3%) across multiple studies ( 164 172 ). A meta-analysis of 11 studies found SISCOM accurately localized seizure focus in 85.9% of cases and was concordant with EEG data in 65.3% of cases ( 166 ).…”
Section: Assessment Of the State Of The Art—spect In Brain Disordersmentioning
confidence: 99%
“…Artificial intelligence has made tremendous and remarkable progress in the health field [51], as it facilitates many of the problems related to filling out forms for admission in hospitals or clinics and preventing the surge of discounts at the reception desk. In recent times, the science of artificial intelligence has been able to contribute to the development of the healthcare system to be more effective in detecting diseases such as cancer [52], infections [53][54][55][56], and other diseases, in addition to the development of robots that perform surgeries and accurate diagnosis [57,58]. Recent statistics indicate that artificial intelligence developers have arrived at the stage of providing effective solutions to complex obstacles in healthcare management systems, thereby revolutionizing the medical field to eliminate inefficient systems prevailing in societies.…”
Section: The Importance Of Artificial Intelligence In Healthcare and ...mentioning
confidence: 99%
“…There are a large number of investigations in which artificial intelligence techniques have been used in analysing medical data, whether images or texts, due to the significance of these technologies in healthcare. From 2019 until August 2022, many investigations appeared in the application of machine learning and deep learning techniques in diagnosing COVID-19 diseases through chest X-rays and comparing the performance and practices of these techniques in analysing the most significant number of images [77][78][79][80][81]. Analyses based on machine learning in the field of diagnosis focus on many diseases, including heart disease, cancer, kidney disease, and Alzheimer's.…”
Section: Digitalisation and Ai In Healthcarementioning
confidence: 99%